SPECTROSCOPIC CHARACTERIZATION OF PHYTOCONSTITUENTS ISOLATED FROM A RARE MANGROVE AEGIALITIS ROTUNDIFOLIA ROXB., LEAVES AND EVALUATION OF ANTIMICROBIAL ACTIVITY OF THE CRUDE EXTRACT - DEBJIT GHOSH; SUMANTA MONDAL; K. RAMAKRISHNA (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The aim of the study is to isolate and characterize the phytochemicals from the leaves of a rare and unexplored mangrove Aegialitis rotundifolia and evaluate the antimicrobial properties of the crude extract. Methods: The dried powdered plant material was extracted with ethanol, and the ethanol extract obtained was dissolved in distilled water and partitioned using n-hexane first and then ethyl acetate. The ethyl acetate fraction was subjected to column chromatography for isolation of phytocompounds. The isolated compounds were characterized using infrared (IR), carbon-13 nuclear magnetic resonance (13C NMR), proton nuclear magnetic resonance (1H NMR), mass spectroscopy, and thin-layer chromatography (TLC). Antimicrobial activity of the crude extracts was performed using the well diffusion method against four bacterial strains and two fungal strains. Results: Three pure compounds were isolated from the leaves of Aegialitis rotundifolia, namely, 3,4-dimethyl benzoic acid, 3’-methoxy-4’-hydroxy-flavan-3-ol, and 3’,7-dimethoxy-dimethyl-4’,3,5-trihydroxy flavone which were confirmed by spectroscopic studies. Strong antibacterial activity was shown by the test extract against Staphylococcus aureus and Pseudomonas aeruginosa, whereas Escherichia coli and Bacillus cereus showed average and nil activity, respectively. The antifungal activity of the test extract was found to be strong for both the fungal strains, namely, Candida albicans and Aspergillus niger. Conclusion: The results of the present study show that the isolated compounds were confirmed to be 3,4-dimethyl benzoic acid, 3’-methoxy-4’- hydroxy-flavan-3-ol, and 3’,7-dimethoxy-dimethyl-4’,3,5-trihydroxy flavone and the test extracts showed potent antimicrobial activity for all the bacterial and fungal strains except E. coli and B. cereus which showed average and nil activity, respectively.